Electricity and energy policy in Britain, France and the United States since 1945 - Chick, Martin, 1958-; Edward Elgar Publishing (Cheltenham ; Northampton, Mass. : Edward Elgar, 2007)
Martin Chick's book is a major economic and historical study of the development of electricity and energy policy in Britain, France and the United States since 1945. Using newly available archival material the author draws important comparisons between these countries and includes all of the fuel and power industries.
Introduction -- Shifting from coal to oil : what price security? -- The European coal and steel community -- Moving the margin to the centre : pricing electricity -- Electricity investment : rewarding the past, discounting the future -- Deregulation, privatisation and liberalisation -- Conclusion.
Includes bibliographical references (p. 169-193) and index.
Keywords: Energy policy -- Great Britain -- History -- 20th century; Energy policy -- France -- History -- 20th century; Energy policy -- United States -- History -- 20th century; Electric utilities -- Great Britain -- History -- 20th century; Electric utilities -- France -- History -- 20th century; Electric utilities -- United States -- History -- 20th century; Electronic books